Incremental validity of acceptance over coping in predicting adjustment to endometriosis - Bernini, Olivia; Tumminaro, Giovanni; Compare, Lisa; Belviso, Cristina; Conforti, Valentina; Berrocal Montiel, Carmen (Frontiers in Pain Research, 2022)
Psychological acceptance has emerged as an important construct to explain low psychological distress in different clinical samples. However, the incremental validity of psychological acceptance to explain adjustment to medical conditions over other related and well-established constructs, such as coping, is relatively unclear. This study explored whether psychological acceptance significantly contributes to explain adjustment above and beyond coping in females with endometriosis. A total of 169 females (Mage = 34.95 years; SDage = 6.07 years) with endometriosis and pain symptoms completed the Acceptance and Action Questionnaire-II, the Brief-COPE, the Hospital Anxiety and Depression Scale, the Psychological Wellbeing Scale, and the Endometriosis Health Profile-5. We conducted Hierarchical Regression Analyses to determine the contribution of psychological acceptance to explaining adjustment. The results showed that the contribution of psychological acceptance ranged from 11 to 20% when controlling for coping, while coping explained from 1 to 8% when the model was reversed. The findings suggest that psychological acceptance is a more useful construct than coping for predicting PD and other psychological outcomes in females with endometriosis.